Building Industrial Digital Twins: Design, develop, and deploy digital twin solutions for real-world industries using Azure Digital Twins - Varan Nath, Shyam; Schalkwyk, Pieter van (Packt Publishing, 2021)
Build your first digital twin MVP and gain first-hand experience of using the technology, the challenges it presents, and its impact on your organization Key Features Create a digital twin prototype using Microsoft Azure Digital TwinExplore the digital twin approach to the design, operations, and maintenance of industrial assets and productsUnderstand key characteristics and components of a digital twin through practical use cases and business scenarios Book Description Digital twin technology enables organizations to create digital representations of physical entities such as assets, systems, and processes throughout their life cycle. It improves asset performance, utilization, and safe operations and reduces manufacturing, operational, and maintenance costs. The book begins by introducing you to the concept of digital twins and sets you on a path to develop a digital twin strategy to positively influence business outcomes in your organization. You'll understand how digital twins relate to physical assets, processes, and technology and learn about the prerequisite conditions for the right platform, scale, and use case of your digital twins. You'll then get hands-on with Microsoft's Azure Digital Twins platform for your digital twin development and deployment. The book equips you with the knowledge to evaluate enterprise and specialty platforms, including the cloud and industrial IoT required to set up your digital twin prototype. Once you've built your prototype, you'll be able to test and validate it relative to the intended purpose of the twin through pilot deployment, full deployment, and value tracking techniques. By the end of this book, you'll have developed the skills to build and deploy your digital twin prototype, or minimum viable twin, to demonstrate, assess, and monitor your asset at specific stages in the asset life cycle. What you will learn Identify key criteria for the applicability of digital twins in your organizationExplore the RACI matrix and rapid experimentation for choosing the right tech stack for your digital twin systemEvaluate public cloud, industrial IoT, and enterprise platforms to set up your prototypeDevelop a digital twin prototype and validate it using a unit test, integration test, and functional testPerform an RoI analysis of your digital twin to determine its economic viability for the businessDiscover techniques to improve your digital twin for future enhancements Who this book is for The digital twin book is for mid-career subject experts, including engineers and operations managers, building their first prototype (MVP) using digital twin technology. The book will help professionals responsible for mechanical, process, and reliability engineering domains. You don't have to be a developer or programmer, but beginner-level programming skills will be helpful.